2022
DOI: 10.1159/000523822
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Intravascular Coagulation with Enhanced Fibrinolysis Caused by Heart Metastasis of Bladder Urothelial Carcinoma

Abstract: Heart metastases from urothelial carcinoma of the bladder have rarely been reported in the literature. We present a case complicated by symptomatic disseminated intravascular coagulation in a 67-year-old woman. A rapid and sustained recovery from hemostatic troubles was obtained following fibrinogen supplementation combined with second-line paclitaxel chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The analysis of 20 studies, plus our case report totaled 30 patients described between 1934 and 2023, proving the rarity of cardiac metastasis of TCC [ 2 , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Data in showed that patients with cardiac metastasis from TCC are predominantly men (77.78 %), mean age 65.47 years, most patients were diagnosed after death by autopsy (57.90 %) ( Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The analysis of 20 studies, plus our case report totaled 30 patients described between 1934 and 2023, proving the rarity of cardiac metastasis of TCC [ 2 , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Data in showed that patients with cardiac metastasis from TCC are predominantly men (77.78 %), mean age 65.47 years, most patients were diagnosed after death by autopsy (57.90 %) ( Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Caucasian ethnicity, and comorbidities such as exposure to smoking and arterial hypertension were more prevalent. Only 10 studies [ 2 , [9] , [10] , [11] , [12] , [14] , [15] , [16] , 18 , 23 ] report the TNM staging profile of TCC bladder cancer, with tumors T1 (20.00 %), T2 (10.00 %), T3 (50.00 %), T4 (20.00 %), WHO classification in grade 2 (12.50 %), grade 3 (75.00 %), grade 4 (12.50 %). The size of the primary bladder mass ranged from 2.0 cm to 7.3 cm and a mean of 4.32 cm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations